Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Minyak Goreng di Pasar Tente Kabupaten Bima - Kurniawan Kurniawan; Amirulmukminin Amirulmukminin; Nur Khusnul Hamidah (Indo Publishing, 2026)
This study aims to determine the effect of price and brand image on purchasing decisions for cooking oil at Tente Market, Bima Regency, both partially and simultaneously. This research employed a quantitative approach with an associative research design. The population consisted of consumers who had purchased cooking oil at Tente Market, Bima Regency, with an unknown population size. The sample comprised 96 respondents selected using a purposive sampling technique. Data were collected through observation, questionnaires using a Likert scale, and literature review. The data were analyzed using SPSS version 22, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-tests, and F-tests. The results showed that the price variable had a positive and significant effect on purchasing decisions, with a t-value of 5.372 and a significance value of 0.000 (<0.05). The brand image variable also had a positive and significant effect on purchasing decisions, with a t-value of 3.375 and a significance value of 0.001 (<0.05). Simultaneously, price and brand image had a significant effect on purchasing decisions, with an F-value of 31.877 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) was 0.407, indicating that price and brand image explained 40.7% of the variation in purchasing decisions, while the remaining 59.3% was influenced by other variables not examined in this study.